If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-147=7(-4n+3)
We move all terms to the left:
-147-(7(-4n+3))=0
We calculate terms in parentheses: -(7(-4n+3)), so:We get rid of parentheses
7(-4n+3)
We multiply parentheses
-28n+21
Back to the equation:
-(-28n+21)
28n-21-147=0
We add all the numbers together, and all the variables
28n-168=0
We move all terms containing n to the left, all other terms to the right
28n=168
n=168/28
n=6
| 4x+5(2x-3)=69 | | -9+x/7=-3 | | 0.8x−2=0.48x+6 | | (17+x)2+6x=90 | | (8-3x)5+5x=60 | | n/4=-2.7 | | (x(4-3x)+4(x^2+1))/x^2-4=0 | | 45x-33x+19=25+17 | | 12m+6=15m-3 | | 2x=(90/4) | | 6m+3=29; | | (7-x)5+7x=73 | | 10=-4p-6p | | 6y+1=3y+28 | | 15/18y+1=−6/18y+10/18 | | 5/6y+1=−1/3y+5/9 | | (x)=−3x^2+75 | | −2x^2−9+107=0 | | 160(x-3)=100x | | (3-4x/6)-(2x-3/8)=2-x | | y-4.7=18.6 | | 120=0.30-6x | | -8a-1=2-5a | | 4x+4x^2+3+3x=0 | | 4x+4x^2+3+3x=) | | X+5x-15=x+235 | | 1.4x+3=17 | | 6x+3=9+8x | | 5x+3=6x+15 | | 2x,-3=0 | | 5/6x=8=-11 | | (5x+9x+6x)-(-9x-20x-+6x)=0 |